Reação de mercado associada à disponibilidade de informação - Sebbag, Ariel (2010)
Behavioral finance theory is sustained by two grand pillars: limits of arbitrage and investor irrationality. Among the known rationality biases, one was of particular interest to this study: the availability bias. This bias happens on the situations in which people assess the frequency of a class or the probability of an event by the ease with which instances or occurrences can be brought to mind. The advent of the Internet allowed the large scale verification of the availability bias through the analysis of the search engines data. I.e., if a certain stock is more looked for than others, we can infer that it is more available in the collective memory of the investors. On the other hand, the behavioral finance literature has a more pragmatic arm, which studies stategies capable to offer abnormal returns, above what is expected by the efficient market hypothesis. This study focuses on the momentum effect, where the portfolio of equities formed with the best performers from the last J months tends to perform better for the next K months than the portfolio of all the other equities. The purpose of this study was to assess the possibility of obtaining returns above those identified by the momentum effect by segmenting the portfolio among equities more or less affected by the availability bias, as given by the Internet search data analysis. The results were positive and statistically significant on the selected sample. The combined strategy among momentum effect and availability data produced, for J=6 e K=6, abnormal monthly returns of 2,82% with t-statistics of 3,14. The momentum effect alone for the same formation and holding period generated average returns of only 1,40% with t-statistics of 1,22